Augmentative and Alternative Communication (AAC) for Autism Spectrum Disorders (ASD) Children's Language and Communication - Luh Diah Surya Adnyani; Ahmad Munir (PAROLE: Journal of Linguistics and Education, 2022)
Augmentative and Alternative Communication (AAC) is an expressive and receptive method of communication that helps in developing language and communication skills for people with speech and/or language impairment.   Autism spectrum disorders (ASD) children who lack communication can improve functional communication by personalizing AAC intervention. This paper is based on literature to promote AAC interventions to enhance English language acquisition in autism spectrum disorder (ASD) children. This paper also explores how multimodal and naturalistic AAC benefit ASD children's communicative and language skills. Recommended herewith is to personalize AAC intervention based on children's mental and physical condition and their needs, skills, and social environment's priority.